THE EFFECTIVENESS OF THE DEVELOPMENT OF GROSS MOTORIC SKILLS AMONG PRESCHOOL CHILDREN BETWEEN PRE AND POST STIMULATION OF TRADITIONAL ENGKLEK GAMES - Rose, Andiny; Rahmaningtyas, Indah; Rahayu, Dwi Estuning; Antono, Sumy Dwi (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Gross motoric skills are essential abilities during preschool children's development, involving significant body movements such as running, jumping, and maintaining balance. One traditional Indonesian game, called “engklek”, is believed to support the development of children's gross motor skills. A lack of gross motor stimulation can negatively impact the child's growth and development. Therefore, it is crucial for parents, teachers, and guardians to ensure children engage in activities that stimulate gross motoric skills. Method: This study employed a pre-experimental design, specifically using a one-group pre-test and post-test design. The population consisted of 39 preschool children, with 36 respondents randomly selected through simple random sampling. The instrument used in this study was the traditional game of ”engklek” to collect data, with pre-tests and post-tests conducted to measure the respondents' ability to lift their legs according to their age. Data were analyzed using the Wilcoxon signed-rank test, with significant results (p < 0.005).Results: The final results showed that stimulation using the traditional “engklek” game positively impacted the gross motor development of preschool children aged 5 to 6 years at Al-Amin Kindergarten in Kediri City. Discussion: This study will highlight the importance of paying attention to gross motor stimulation in preschool children, including through traditional games like “engklek”. It will also emphasize the need to monitor children's gross motor development according to their age to ensure optimal progress